EFFECT OF DIFFERENT ORGANIC MULCHING MATERIALS ON SOIL PROPERTIES OF NA ‘7’ AONLA (EMBLICA OFFICINALIS GAERTN) UNDER RAINFED CONDITION OF SHIWALIK FOOTHILLS OF HIMALAYAS INDIA - KUMAR, VIJAY (The Bioscan, 2014)
An experiment was conducted during 2009-2011 to assess the effected different organic mulches (Bajra straw, Maize straw, Palah leaves (Butea monosperma), Branker (Adhatoda vassica), Farmyard manure) on soil properties in NA ‘7’ aonla (Emblica officinalis Gaertn). Different organic mulches significantly increased the soil organic carbon and nutrients. Soil properties were highest in FYM and lowest in control. In the present study the effect of mulching type on soil characters including soil pH, EC, OC, Available N, P and K was evaluated during two years. This research was conducted as randomized block design with four replications. In this study, soil pH, OC (organic carbon), EC, N, P and K in 0 to 15 cm soil depth was measured. Results showed that effect of type of mulch on soil pH and soil EC was not significant among all the treatments, while on OC (organic carbon), N, P and K was significant in all treatments. Farmyard manure mulch recorded highest soil organic carbon (6.60 and 6.80 g kg-1), Soil available nitrogen (238.00 and 239 kg ha-1), Soil available Phosphorus (20.12and 21.00 kg ha-1) and Soil available Potassium (169.92 and 179.48 kg ha-1) in 2009 and 2010 followed by branker (Adhatoda vassica). Maize straw mulch with 0-15 cm thickness has the highest reduction of soil pH and EC in all types of mulch. FYM with 0-15 cm thickness has the highest percentage of OC, N, P and K. Farmyard manure and Branker (Adhatoda vassica) have the greatest effect on soil organic carbon and available nutrients.